2011
DOI: 10.1017/s0266467411000617
|View full text |Cite
|
Sign up to set email alerts
|

Tree species distribution in Andean forests: influence of regional and local factors

Abstract: Abstract:We identified and quantified regional and local environmental factors and spatial variation associated with tree-species composition across a 2000-m altitudinal gradient of Andean forest in north-western Argentina. A network of 47 1-ha plots was established along the altitudinal gradient within an area of about 25 000 km2; all trees ≥ 10 cm dbh were identified and measured. Constrained ordinations and variance-partitioning analyses were performed to investigate the determinants of tree-species distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 49 publications
1
34
0
11
Order By: Relevance
“…fraction of animal dispersed vs wind dispersed fruits) an abiotic (e.g. moisture stress) factors (Blundo et al, 2012;Malizia et al, unpublished results). In other tropical systems the diversity of mammals and the species composition of the mammal assemblage change along ecological gradients that vary is tree species composition and structural complexity (August, 1983;Williams et al, 2002;Tews et al, 2004) Thus, we expected to find the observed pattern of mean species richness per cameratrap station decreasing with elevation and the correlation between elevation and the NMDS ordination.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…fraction of animal dispersed vs wind dispersed fruits) an abiotic (e.g. moisture stress) factors (Blundo et al, 2012;Malizia et al, unpublished results). In other tropical systems the diversity of mammals and the species composition of the mammal assemblage change along ecological gradients that vary is tree species composition and structural complexity (August, 1983;Williams et al, 2002;Tews et al, 2004) Thus, we expected to find the observed pattern of mean species richness per cameratrap station decreasing with elevation and the correlation between elevation and the NMDS ordination.…”
Section: Discussionmentioning
confidence: 96%
“…The abundance of both ungulates and top predators is usually higher in the better-protected areas and increases with the distance to the more accessible areas frequented by poachers (e.g., Caro, 1999;Di Bitetti et al, 2008, 2010. Livestock grazing is an activity that usually has notorious effects on the structure and composition of natural communities (Cingolani et al, 2008;Blundo et al, 2012). Among the mammals, large herbivores may be negatively affected by cattle through competitive interactions (Madhusudan, 2004;Hibert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, altitudinal variations comprise a complex set of variables related to temperature, air humidity, water availability, wind exposure, in addition to soil depth and drainage classes HOMEIER et al, 2010;BLUNDO et al, 2012).…”
Section: A Abiotic Descriptorsmentioning
confidence: 99%
“…2012), for example, through its influence on climate conditions such as temperature and precipitation (Blundo et al. 2012; Krömer et al. 2013; Li et al.…”
Section: Introductionmentioning
confidence: 99%